2011
DOI: 10.1186/1556-276x-6-390
|View full text |Cite
|
Sign up to set email alerts
|

Reliable processing of graphene using metal etchmasks

Abstract: Graphene exhibits exciting properties which make it an appealing candidate for use in electronic devices. Reliable processes for device fabrication are crucial prerequisites for this. We developed a large area of CVD synthesis and transfer of graphene films. With patterning of these graphene layers using standard photoresist masks, we are able to produce arrays of gated graphene devices with four point contacts. The etching and lift off process poses problems because of delamination and contamination due to po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 11 publications
5
33
1
Order By: Relevance
“…Furthermore Fig. 4b shows the corresponding output characteristic which exhibits the typical three region behavior of a large area monolayer graphene transistor as described in [23], confirming the existence of transfer-free and in-situ CCVD grown and [24] as well as in our work.…”
Section: B Electrical Characterizationsupporting
confidence: 67%
“…Furthermore Fig. 4b shows the corresponding output characteristic which exhibits the typical three region behavior of a large area monolayer graphene transistor as described in [23], confirming the existence of transfer-free and in-situ CCVD grown and [24] as well as in our work.…”
Section: B Electrical Characterizationsupporting
confidence: 67%
“…Changing the sweep direction shifts the Dirac point from V BG = -6V to V BG = 11V which is equivalent to a hysteresis of ΔV BG = 17 V. Lemme [6] reports a hysteresis of ΔV BG = 22 V for a front gated MoLGFET on silicon dioxide substrate. Top contacted graphene ribbons on Al 2 O 3 substrate are examined by Kumar et al [7], exhibiting a hysteresis of ΔV BG ~ 20 V. Wang et al [8] show current voltage characteristics exhibiting a positive hysteresis of the same order of magnitude as found in both [6] and [7]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, since single-layer graphene is oneatom thick, any residues from fabrication can significantly influence charge transport and electronic device performance. [11][12][13][14][15][16] Although several studies have reported dry etching procedures for graphene-based devices, [17][18][19][20][21][22][23][24][25] this previous work primarily employed optical microscopy and Raman spectroscopy to determine optimal etching conditions. While these methods provide valuable information, they lack sufficient resolution and/or sensitivity to definitively detect residual graphene and/or etching byproducts at the nanoscale.…”
Section: Manuscriptmentioning
confidence: 99%